2011
DOI: 10.1097/eja.0b013e32834698f4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of head and neck position on ventilation with the i-gel airway in paralysed, anaesthetised patients

Abstract: Effective ventilation with an i-gel can be performed in patients in whom the head and neck is extended or rotated, whereas flexion of the head and neck adversely affects ventilation. Clinically, flexion of the head and neck should be avoided during ventilation with the i-gel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 8 publications
4
48
2
Order By: Relevance
“…However, two previous studies showed that the success rate of i-gel insertion is high, even for novices [8,17]. We also think that our results can be generalised because the success rate, insertion time, and seal pressure in the standard technique group were similar to data from other experienced operators [8,10,21].…”
Section: Discussionsupporting
confidence: 63%
“…However, two previous studies showed that the success rate of i-gel insertion is high, even for novices [8,17]. We also think that our results can be generalised because the success rate, insertion time, and seal pressure in the standard technique group were similar to data from other experienced operators [8,10,21].…”
Section: Discussionsupporting
confidence: 63%
“…Several clinical studies have shown that the i-gel effectively conforms to the perilaryngeal anatomy and consistently achieves proper positioning for supraglottic ventilation [14,15]. SGDs are also suited for difficult airway management, especially in "cannot intubate, cannot ventilate" situations [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Sanuki et al [10] started the evaluation of effectiveness of head and neck positions on ventilation on I-gel airway devices, as they investigated the effect of different positions on oropharyngeal leak pressure and ventilation scores during ventilation with I-gel. Compared with the neutral position (25.8±5.2cm H 2 O), oropharyngeal leak pressure was significantly higher with flexion (28.5±3.4cm H 2 O, P=0.015) and lower with extension (23.0±4.2cm H 2 O, P=0.015), but similar with rotation (26.7±5.1 cm H 2 O, P=0.667).…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated, with a confidence interval of 95% and a power of 90%, based upon previous studies [10,15]. The maximum sample size was 30 in each group for flexion with a difference between means of 4 cm of H 2 O for oro-pharyngeal leak pressures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation